TMA Vessel Segmentation Based on Color and Morphological Features: Application to Angiogenesis Research - M. Milagro Fernández-Carrobles; Irene Tadeo; Gloria Bueno; Rosa Noguera; Oscar Déniz; Jesús Salido; Marcial García-Rojo (The Scientific World Journal)
Given that angiogenesis and lymphangiogenesis are strongly related to prognosis in neoplastic and other pathologies and that many methods exist that provide different results, we aim to construct a morphometric tool allowing us to measure different aspects of the shape and size of vascular vessels in a complete and accurate way. The developed tool presented is based on vessel closing which is an essential property to properly characterize the size and the shape of vascular and lymphatic vessels. The method is fast and accurate improving existing tools for angiogenesis analysis. The tool also improves the accuracy of vascular density measurements, since the set of endothelial cells forming a vessel is considered as a single object.